IMPLEMENTASI PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KETERLIBATAN SISWA SEKOLAH DASAR - Mustofa, Ma'ruf; Alfan, Muhammad; Arifin, Slamet (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The aim of this research is to find out whether there is a comparison of the increase in critical thinking skills and student engagement between students who study using the teaching at the right level (TARL) approach and students who study using the conventional approach. The approach used in this research is mixed method. Based on the results of descriptive data analysis for the experimental class, the mean score for the students' pretest = 53.46 and posttest = 83.46. while in the control class the results were the student's average pretest score = 51.53 and the posttest = 75.36. This means that there is a difference in the increase in students' critical thinking abilities before and after being given learning using the TaRL approach. Meanwhile, the results of student involvement in the experimental class are that students can actively participate in class discussions, students can ask questions to obtain further information, students can work independently, students can solve problems flexibly, and students want to get satisfactory grades. Meanwhile, in the control class, the indicators achieved are fewer, namely students can ask questions to get further information, students can get to know teachers at school, students can work independently, so it can be concluded that there is a significant difference in increasing critical thinking skills and student involvement between students who study with the TARL approach and students who study with the conventional approach.